Sistem Informasi Manajemen Klinik Universitas Jambi Guna Mendukung Operasional Klinik - Fairuz Fairuz; Rizqa Raaiqa Bintana; Novita Sari (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Generally, what is found in the clinic includes, registration, doctor consultation, procedure room, laboratory, and pharmacy. The same is true for the facilities available at the Jambi University clinic. All of these are managed by the Jambi University clinic and must be integrated so that all data is united into one information unit. Officers are required to be able to manage all data and manage the clinic well so that no data or information is lost, especially medical records and documents for each patient who is being treated. Therefore, the Information and Communication Technology Development Institute (LPTIK) as an institution at the University of Jambi that is tasked with carrying out information and communication technology development activities wants to help optimize clinic management activities through the development of a clinic application where this application is able to store and manage all data related to the clinic, especially patient data visiting the Jambi University clinic. Thus, the recording and recording of data in the clinic which is currently done manually, can slowly be abandoned towards electronic management activities based on applications. It is hoped that this application-based management activity can help and facilitate clinic officers in managing the clinic, reduce the risk of data loss due to human error or disaster, improve clinic performance, and integrate clinic data as a whole. The UNJA Clinic application was built to facilitate and facilitate all activities related to recording and recording data in the clinic digitally so that the data is fully integrated from several existing parts. The UNJA Clinic application that has been built is a website-based application.